Climate-related disaster risk in mountain areas: the Guatemalan highlands at the start of the 21st Century - Guerra Noriega, AA (2010)
Mountains are hazardous places. Framed in political ecology and disaster theory in geography, this research set out to answer the overarching question of how the risk of climate-related disasters has changed in mountain areas of Guatemala at the start of the century. It involved four main related activities that examined key elements of disaster risk: 1) the trigger, assessing extreme rainfall trends based on daily records; 2) the hazards, through an evaluation of the relevance of land use and cover (LUC) to slope failure; 3) elements of social vulnerability, looking at its geography and trend at the turn of the century, and also exploring the role of globalisation in specific communities; and 4) an assessment and mapping of disaster risk in two sites, including an estimation of exposure levels to hazards. Methods range from statistical analysis of quantitative data (rainfall, landslide, and vulnerability chapters), GIS-based modelling (risk mapping), and qualitative analysis including interviews. The main findings state that: increasing annual and extreme rainfall has contributed to higher disaster risk only in a few areas; LUC change from forest to annual crops has increased risk in a few locations but it has not done so in most of the volcanic highlands either because there has been only minor LUC change or because LUC does not seem to have an effect on slope failure in certain types of geology. Disaster risk has decreased overall because vulnerability has become lower in the vast majority of mountain areas but risk may be higher as a result of increased exposure to hazards either in mountain communities or in marginal areas of the capital and surrounding municipios. The analysis of risk helped identify four mountain zones where risk is very likely to have increased. Further research questions are mostly related to studying the evolution of climate-related disaster risk in those areas.